2013
DOI: 10.1111/cts.12121
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Increases Muscle Protein Synthesis and Reduces Muscle Fatigue

Abstract: Reductions in skeletal muscle function occur during the course of healthy aging as well as with bedrest or diverse diseases such as cancer, muscular dystrophy, and heart failure. However, there are no accepted pharmacologic therapies to improve impaired skeletal muscle function. Nitric oxide may influence skeletal muscle function through effects on excitation-contraction coupling, myofibrillar function, perfusion, and metabolism. Here we show that augmentation of nitric oxide-cyclic guanosine monophosphate sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Percival et al (38) showed that a 14-wk treatment with sildenafil reduced respiratory muscle weakness and fibrosis in the mdx mouse model of Duchenne muscular dystrophy. In humans, a recent study documented that sildenafil administration for 8 consecutive days nearly doubled skeletal muscle protein synthesis and reduced muscle fatigue in healthy subjects (45). On the basis of these observations, future studies are needed to verify the long-term consequences of regular sildenafil administration in patients with IC.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Percival et al (38) showed that a 14-wk treatment with sildenafil reduced respiratory muscle weakness and fibrosis in the mdx mouse model of Duchenne muscular dystrophy. In humans, a recent study documented that sildenafil administration for 8 consecutive days nearly doubled skeletal muscle protein synthesis and reduced muscle fatigue in healthy subjects (45). On the basis of these observations, future studies are needed to verify the long-term consequences of regular sildenafil administration in patients with IC.…”
Section: Study Limitationsmentioning
confidence: 99%
“…23,[25][26][27][28][29] In addition, unlike smooth muscle, most sildenafil studies on skeletal muscle were conducted at macroscopic levels, such as physiological aspects of tissues or Figure 4 Ca 2+ movement in primary skeletal myotubes. Caffeine (a), which is a direct RyR1 agonist or KCl (b), a membrane depolarizer, was applied to myotubes treated with sildenafil, and Ca 2+ movement from the SR to cytosol in myotubes was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil lowers blood pressure by dilating blood vessels, [20][21][22] it improves skeletal muscle oxygenation during exercise in patients with intermittent claudication, 29 and it ameliorates skeletal muscle fatigue in a mouse DMD model and in healthy men. 23,24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents include the sublingual and transdermal nitrates, intravenous propionyl-L-carnitine, intravenous L-arginine, and other medications used for the treatment of erectile dysfunction (e.g., phosphodiesterase-5 inhibitors). Related to the latter, although specifically prescribed for purposes of improving erectile function, evidence indicates the potential role of a phosphodiesterase-5 inhibitor (Sildenafil) to impact outcomes related to physical performance and adaptations to regular exercise (Hsu et al, 2006;Rinaldi et al, 2013;Sheffield-Moore et al, 2013). This fact suggests the likelihood that phosphodiesterase-5 inhibitors are now being used within the athletic doping world.…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%